Limitations for the conferral of fiscal competences emerging from the rule of law and the principle of democracy - Rozenšteina, Madlēna Melinda (Riga Graduate School of Law, 2018)
This research is aimed at answering the question of whether the conferral of fiscal competences necessary to facilitate further integration of fiscal policies in the European Union is possible in the light of the current state of affairs in Europe. Accordingly, the hypothesis that is tested is that the conferral of fiscal competences would not be possible as a respect for the rule of law and the principles of democracy require that such a reform, in most countries, must gain the support of the public through a referendum, which may be difficult to pass due to prevailing public sentiment on the issues involved. The research affirms the hypothesis and establishes that it would be unlikely to facilitate the necessary reforms mainly due to the current political environment of the European Union.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; European monetary policy